Dynamic response of a fluid-saturated elastic porous solid - Breuer, S. (Archives of Mechanics, 1997)
In this paper, the field equations governing the dynamic response of a fluid-saturated elastic porous media are analyzed and built up for the study of the consolidation problem and the one-dimensional wave propagation. The two constituents are assumed to be incompressible. A one-dimensional numerical solution is derived by means of the standard Galerkin procedure and the finite element method. As a result of the incompressibility, there is only one independent dilatational wave propagating in the solid and the fluid phase. This work can provide further understanding of the wave propagation in porous materials, not only in view of the propagation speed, but also with respect to the development of the amplitudes.